Thematic-Based Interactive Learning Multimedia In Early Childhood Language Development - Raisah Armayanti Nasution; Sholihatul Hamidah Daulay; Nanda Novita (Universitas Pendidikan Ganesha, 2023)
Language development still applies conventional learning without using learning media such as interactive learning multimedia. So this study aims to develop thematic-based interactive learning multimedia in early childhood language development. This research belongs to the type of ADDIE development model development research. The subjects involved in this study were material experts, media experts, and 83 early childhood children—data collection using the method of observation, interviews, and questionnaires. The research instrument used was the validity sheet. The data obtained in the study were then analyzed using a descriptive presentation analysis with a questionnaire to experts to test the feasibility and analysis of the data to test the effectiveness of using the Normalized Gain test (N-gain score). The results of the data analysis show that the product feasibility test, with a percentage of 93.47% by material experts and 85.71% by media experts, is included in the very feasible category. The effectiveness test results have met the effective category seen from the acquisition of the average value according to the calculation of the N-Gain score. It was concluded that thematic-based interactive learning multimedia is valid and feasible to develop because it can maximize children's language development.